2017
DOI: 10.1093/icvts/ivx229
|View full text |Cite
|
Sign up to set email alerts
|

Acute DeBakey Type I aortic dissection without intimal tear in the arch: is total arch replacement the right choice?

Abstract: TAR was associated with higher 30-day mortality compared with the less extensive hemiarch replacement. In the long term, TAR showed a trend of improved survival and higher reintervention rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In 2018 Colli and colleagues performed surgical approaches on patients with Stanford A AAD without intimal tear in the aortic arch and found that patients with total aortic arch repair suffered from a higher 30-day mortality. 34 However longterm mortality in the total aortic arch repair group was similar to the ascending and hemiarch repair groups. These results corroborate our results focusing on less invasive or aggressive surgical procedures.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In 2018 Colli and colleagues performed surgical approaches on patients with Stanford A AAD without intimal tear in the aortic arch and found that patients with total aortic arch repair suffered from a higher 30-day mortality. 34 However longterm mortality in the total aortic arch repair group was similar to the ascending and hemiarch repair groups. These results corroborate our results focusing on less invasive or aggressive surgical procedures.…”
Section: Discussionmentioning
confidence: 75%
“…Latest studies published by Colli and colleagues in 2018 and 2016 34,35 and by Russo and colleagues 37 revealed that despite substantial progress in surgical techniques and perioperative management, the best surgical approach for patients suffering from Stanford A dissection is still controversial and outcomes highly dependent on perioperative risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Crack growth was also measured after the experiment. Aortic dissection is most commonly associated with an intimal tear or notch [53,[57][58][59], however it can and does occur (although less commonly) without a visible entry tear in certain cases [60][61][62][63]. This is reflected in the results of our study, all samples tested with a radial notch exhibited extensive mode II crack growth whereas only 3 out of 8 samples with a circumferential notch exhibited mode II crack growth.…”
Section: Appendix A: Artery Materials Modelmentioning
confidence: 49%
“…Average crack length was 11.79mm+/− 4.1mm. Aortic dissection is most commonly associated with an intimal tear or notch [33,[37][38][39], however it can and does occur (although less commonly) without a visible entry tear in certain cases [40][41][42][43]. This is reflected in the results of our study, all samples tested with a radial notch exhibited extensive mode II crack growth whereas only 3 out of 8 samples with a circumferential notch exhibited mode II crack growth.…”
Section: Appendix A: Artery Materials Modelmentioning
confidence: 49%